A Study On The Expression Of Mockery In Eminem's "The Eminem Show" Songs Lyric: Pragmatics Approach - Suryani, Rosaria (2004)
The study is about the expression of mockery. Mockery is the act of mocking, deriding and exposing to contempt by mimicry, by sincere imitation, by a false show of earnest, or a counterfeit appearance. It is interesting to study this expression as people might use several aspects to make their utterance become mockeries. And thus, semantically understanding is not enough here. The data are taken from Eminem's songs from his album The Eminem Show. The objectives of the study are to analyze the objects Eminem use to express mockery on their song lyrics, to analyze what key factors that enable the utterances to cause mockery and to analyze how Eminem express their mockery in their songs. To analyze the key factors of the mockery, the writer uses speech act theory. She discusses what factors that cause the locutionary and the illocutionary act lead to the perlocutionary act. The writer finds out there are 10 kinds of objects Eminem use to express his mockery. They are Eminem's own country, political policy, a conventional rule of a court, the target's relative, the mockerer's own achievement, the target's fondness, the target's physical appearance, the target's age, the target's work and the target's conduct. The study indicates that there are various ways of expressing mockery used by Eminem. They are by making a mistake intentionally, by derision, by showing fake earnest, by satirical mimicry and by showing contempt. There are four key factors in the expression of mockery. They are semantic, political knowledge, social knowledge and inference.